Analisis Praktik Akad Muzara’ah Di Desa Lebak Kecamatan Sangkapura Bawean Gresik Perspektif Hukum Islam - Ainun Barakah; Pipin Suitra (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2019)
Abstract Bawean is an archipelago administratively included in Gresik Regency, where the main occupation of the people is farming and fishing, but not all of the people have land to farm and ships to go to sea, and not a few who work in Malaysia and Singapore have even become citizens of that country. so that the land and rice fields below are unproductive, so there is cooperation between landowners and tenants or cultivators, in agricultural practices, landowners and processors or workers often make contracts and agreements in such cooperation, as well as in the village of Lebak, the agreement sees to the weather, or irrigation used to irrigate rice fields, and the yields obtained during the rainy season in certain months are different, there are at least three cooperation systems in the muzara'ah contract implemented there, in this study the three systems were analyzed to determine which in accordance with Islamic law , of the three, there are two agreements that use the muzara’ah contract, and the other one uses the ijarah agreement or lease agreement. This research uses the library research method with a qualitative inductive approach. Keywords: muzara’ah, Islamic Law, Gresik